The Impact of Human Resource Management (HRM) on Performance in Public Sector - Ab. Aziz, Norazlina; Abdul Majid, Izaidin (2012)
This study confers on the discussion on the Human Resource Management (HRM) practices a strategic dimension in boost performance of public sector. A review of the literature identified five main practices of HRM which are training, performance appraisal, employee participant, compensation and selection. Data are collected from 170 departments in public sector. By using measurement of reliability, validity, ANOVA and Multiple Regression Analysis (MRA) through the five practices that influence the performance in public sector, some interesting results are produced which may be considered for adaption in the public sector administration. Results show that relationship between HRM practices and performance in public sector do exist. Keywords – Human resource management, Performance, Public sector